Masjid dan Literasi Keagamaan: Studi Analisis Sosiologis Gerakan Literasi di Masjid Jendral Sudirman Yogyakarta - Derry Ahmad Rizal; M. Yaser Arafat; Nurul Khorina Seci Vella (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
Mosques are central institutions in Muslim life, and have traditionally focused on religious aspects. However, in the context of an increasingly complex modern society, the role of mosques has evolved to encompass various dimensions of life, including religious literacy. This article aims to conduct a sociological analysis of the literacy movement at the Jendral Sudirman Mosque in Yogyakarta, considering the shifting role of mosques in supporting religious literacy. Through a qualitative approach involving interviews and direct observation, this study explores how the Jendral Sudirman Mosque facilitates literacy programs that not only meet religious needs but also open doors for academic learning. The findings show that the mosque has adopted an academically structured approach in presenting literacy materials, which has successfully attracted the attention of not only parents but also the younger generation, especially students. A sociological analysis was conducted to understand the social, political, and cultural context surrounding the literacy movement at the Jendral Sudirman Mosque. The article reveals that this literacy movement is not an isolated phenomenon but a response to existing social and religious dynamics. In addition, it highlights the important role of the mosque's takmir in leading and driving the literacy initiative as well as bridging the relationship between the mosque and its community. This article makes an important contribution to understanding the evolution of the role of mosques in modern society, particularly in the context of religious literacy. The practical implications of this study are also discussed, including its relevance in guiding the development of literacy programs in other mosques and strengthening the role of mosques as holistic community learning centres.